Dinuclear CuII–CuII and CuI–CuII Complexes of a Compartmental Ligand – Syntheses, Structures, Magnetic, and Catalytic Studies. Issue 28 (31st July 2013) - Biswas, Surajit; Dutta, Arpan; Dolai, Malay; Bhowmick, Indrani; Rouzières, Mathieu; Lee, Hon Man; Clérac, Rodolphe; Ali, Mahammad
Abstract: Dinuclear Cu II –Cu II (1 ) and Cu I –Cu II (2 ) complexes were derived from a new N4 O2 donor compartmental ligand (H2 L) by changing the nature of the Cu precursors used. Single‐crystal X‐ray diffraction studies revealed that the Cu1 site in1 has octahedral geometry and is in the inner compartment of the ligand axially coordinated by two ClO4 – anions, whereas the outer Cu2 ion has square‐pyramidal geometry. In2, there are two copper dinuclear complexes (A and B) in the asymmetric unit; the inner core is occupied by Cu1/Cu3 in the +2 oxidation state in a square‐planar geometry. The Cu2/Cu4 ion occupies the outer sites and has distorted tetrahedral geometry with a +1 oxidation state. Complexes1 and2 were obtained simply by changing Cu(ClO4 )2 in1 to Cu(ClO4 )2 and Cu(bipy)(NO3 )2 in2 ; the bipyridyl (bipy) ligand induces the reduction of Cu II to Cu I, which is trapped in the Cu I –Cu II dinuclear product. The oxidation states of the metal ions were ascertained from charge‐balance considerations as well as from bond valence sum (BVS) calculations. No signature of intervalence charge transfer (IVCT) was observed by spectroscopy (UV/Vis/NIR) as well as from the low‐temperature magnetic studies. This might be because of the presence of two copper centers in two different geometries with a wide separation between them (ca. 3.27 Å). For1, the best fit of the χ T vs. T data to the dimer model gives J / k B = –262(1) K and g av = 2.05(5), which indicates that there is a strong antiferromagnetic coupling between the two Cu atoms. In2, the Cu I center is diamagnetic and, thus, the remaining S = 1/2 Cu II magnetic center follows a Curie law with g = 2.06(5). Under homogeneous conditions, both complexes showed catalytic epoxidation of cyclooctene, styrene, and norbornene to the corresponding epoxides with high selectivities and turnover numbers (TONs), which seem to be slightly better than the reported values for Cu II Schiff base complexes. Abstract : Dinuclear Cu II –Cu II (1 ) and Cu I –Cu II (2 ) complexes derived from a new N4 O2 donor ligand (H2 L) are synthesized and characterized by single‐crystal X‐ray diffraction, UV/Vis spectroscopy, and magnetic measurements. In1, there is strong antiferromagnetic coupling between the Cu atoms. In2, the Cu I ion is diamagnetic and the remaining S = 1/2 Cu II magnetic center follows a Curie law with g = 2.06(5).